COMMUNICATION STRATEGIES; DO THEY DIFFER ACROSS THE STUDENTS’ LEVEL OF LANGUAGE LEARNING ANXIETY? - Nurul Atma; Nosmalasari Nosmalasari (Universitas Negeri Padang, 2016)
Since English is not used as a means of communication in daily life interaction, students usually get difficulties to use it which could possibly trigger their language learning anxiety. This case leads them to use certain strategies in order to keep the conversation going on which so-called communication strategies. In relation to this issue, this survey study aims at investigating communication strategies employed by EFL students pursuing Speaking I course. It attempts to find out whether high-anxiety students employ different communication strategies from that of low-anxiety students. Questionnaire is used to measure the students’ level of anxiety and identify their communication strategies. Identification of communication strategies could train the students to be a strategic learner which is required in foreign language learning.